Assessment of greenness, blueness, and whiteness profiles of a validated HPLC-DAD method for quantitation of Donepezil HCl and Curcumin in their laboratory prepared co-formulated nanoliposomes - Mennah M. Abd Elwahab; Samar Saad; Zeinab A. Sheribah; Nahed El-Enany (BMC Chemistry)
Abstract White and Green Analytical Chemistry are innovative approaches in analytical chemistry that prioritize both sustainability and efficiency. Together, these approaches aim to advance scientific research while minimizing environmental impact and enhancing safety. This integration of environmental consciousness into analytical practices represents a significant step forward in achieving sustainable scientific progress. In the present study, a sensitive eco-friendly HPLC-DAD method was carried out and validated to allow concurrent determination of Donepezil HCl (DPZ) and Curcumin (CUR) in their pure form and laboratory made nano-liposome formulation. Optimum seperation was accomplished by utilising Zobrax Eclipse Plus C18 column (4.6*100 mm,5 μm) with gradient elution of the mobile phase composed of 0.02 M phosphate buffer at pH 3.2 and ethanol at flow rate of 1.5 ml/min. A diode array detector (DAD) was implemented for detection at 273 nm and 435 nm for DPZ and CUR, respectively, with the column oven set at 40 °C. The method was validated according to ICH specifications in terms of accuracy, precision, linearity range, detection and quantification limit. The calibration plots were linear with correlation coefficients (r2) = 0.999 over the range (0.1–100 µg/ml) and (0.1–100 µg/ml) for DPZ and CUR, successively. The validated HPLC-DAD approach was adopted to analyse both medications in laboratory prepared nano-liposomal formulation in which the analytes were successfully quantified with good recovery values and no disrubtion from the added excipients. The investigation of whiteness, blueness, and greenness metrics revealed a major benefit of the suggested approach over previous reported ones.